The implementation of the look east policy and its impact on the community development in Malaysia : an analysis - Nor Azlina Endut,; Rohaini Amin, (Penerbit Universiti Kebangsaan Malaysia, 2021)
The Look East policy is not just a political rhetoric of Tun Dr. Mahathir Mohamad. This policy has been compiled and loaded with various programs to ensure its success. This policy was introduced with the aim of changing the thinking and paradigm so that it is not too obsessed with the West, especially Britain. For this purpose, the study will analyze the continuity of Malaysia’s foreign policy towards Japan has succeeded in molding and forming the Malaysian economy to a high-income nation as well as generating first-class minded people. This study uses a qualitative approach by analyzing secondary data derived from books and articles from international journals to support and compare the opinions of other scholars. It is very important to change the notion that everything that comes from the West is good and replaced as an alternative is to look to the East especially Japan. The implementation of the Look East Policy has seen the Japanese government actively aiding Malaysia to develop infrastructure, trade, industry and technical education. This is a good and positive effort from the Malaysian government to further improve the performance of management and development in this country. In short, the implementation of the Look East Policy has made Malaysia succeed in line with other developed countries. The contributions and cooperation forged through the Look East Policy efforts have given their own impact on socio-economic development and community development in Malaysia.